The role of Punica granatum and Polyamines in regulating cell cycle and cell death against human lung adenocarcinoma cells, A549 - Nik Nur Ashikin binti Nik Abdul Malek (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2016)
Cancer is a complex disease to treat and has poor survival rate. Natural product has shown a promising effect in cancer treatments. Punica granatum or pomegranate has a potential to be a useful cancer preventive agent, however the mechanism of action is unclear. To understand how effective the pomegranate in preventing cancer growth, it is crucial to identify the signaling pathways affected. One possibility is the polyamine pathway which is important in many cells function and its up-regulation of this pathway in cancer makes it a logical target for cancer prevention. Therefore, this study was aimed to evaluate the role of pomegranate and polyamines in regulating cell cycle distribution and cell death mechanisms as well as its anti-proliferative effect in human lung adenocarcinoma cells, A549. The classification of polyamines in pomegranate juice was determined by HPLC analysis. The anti-proliferative effect of pomegranate juice was tested by using MTT assay and the effect of 2% pomegranate juice on A549 cells growth and viability were evaluated by trypan blue exclusion assay. The cellular protein and polyamines content in A549 cells were determined using Lowry assay and HPLC, respectively. The cell cycle distribution and cell death mechanisms were evaluated using flow cytometer. The gene expression was evaluated using quantitative real - time PCR. The study found that pomegranate juice was classified under low polyamine diet. At the concentration range from 0 to 3%, pomegranate juice caused inhibition of A549 cells growth. The inhibitory concentration (IC50) was 1.4% ± 0.23, 1.5% ± 0.14 and 1.4% ± 0.12 after 48, 72 and 96 h exposure, respectively. At the concentration of 2%, inhibition of growth was observed by showing decreased in viable A549 cell number and protein content after 48 h (p<0.05), 72 h (p<0.001) and 96 h (p<0.001) exposure compared to untreated A549 cells. In contrast, the percentage of cells viability remains high and constant. The results also showed a positive correlation between total viable A549 cells number with protein content where the R2 values for untreated and treated were 0.9248 and 0.6523. There were no significant differences in total polyamines content in untreated and treated A549 cells. The study also found that pomegranate juice induced cell cycle arrest at G0/G1 phase and apoptosis via intrinsic pathway following 24 h treatment. Pomegranate juice caused loss of mitochondrial membrane permeability after 48 h (p<0.05) exposure and a release of cytochrome c in cytosol after 24 h (p<0.05) and 48 h (p<0.01) exposure in treated A549 cells. In caspases analysis, it was showed that there was activation of caspase-3 following 72 h (p<0.01) treatment and caspase-9 after 48 (p<0.01) and 72 h (p<0.05) exposure in treated A549 cells. Lastly, gene expression study found that pomegranate juice inhibited the expression of ODC gene after 24 h and 48 h exposure (p<0.001) and SSAT gene after 48 h exposure (p<0.05) in treated A549 cells. From the study, it can be deduced that the suppression of A549 cell growth might not due to modulation of polyamine metabolism. However, pomegranate juice able to cause A549 cell growth inhibition by inducing cell cycle arrest and apoptosis through mitochondrial pathway.